Andrew J. Walker correspondence - Walker, Andrew J.
Chiefly letters written by Walker while serving with the 55th Illinois Infantry during the Civil War.
Union soldier and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Illinois Infantry Regiment, 55th (1861-1865); Illinois -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Educators; Soldiers